Berberine attenuates fructose-induced insulin resistance by stimulating the hepatic LKB1/AMPK/PGC1α pathway in mice - Li, Yucheng (Pharm Biol, 2020)
CONTEXT: Berberine is an alkaloid that possesses various pharmacologic effects. OBJECTIVE: To explore the mechanism of berberine to improve insulin sensitivity in fructose-fed mice. MATERIALS AND METHODS: Sixty male ICR mice were randomly divided into 6 groups (10 mice in each group): control, fructose, pioglitazone (10 mg/kg) and berberine (50, 100, and 200 mg/kg). Except for the control group, the mice received 20% fructose drinking for 10 weeks. Pioglitazone and berberine were orally administered once daily during the last 4 weeks. The insulin sensitivity was evaluated using an oral glucose tolerance test (OGTT). The serum levels of fasting glucose and insulin, blood lipids, and hormones were determined. The hepatic AMP and ATP contents were detected using high performance liquid chromatography (HPLC) analysis, and the protein expression was examined by immunoblotting. RESULTS: Berberine significantly reversed the insulin resistance induced by fructose, including lowering fasting insulin levels (from 113.9 to 67.4) and area under the curve (AUC) during OGTT (from 1310 to 1073), decreasing serum leptin (from 0.28 to 0.13) and increasing serum adiponectin levels (from 1.50 to 2.80). Moreover, berberine enhanced the phosphorylation levels of protein kinase B (PKB/AKT; 2.27-fold) and glycogen synthase kinase-3β (GSK3β; 2.56-fold), and increased hepatic glycogen content (from 0.19 to 1.65). Furthermore, berberine upregulated the protein expression of peroxisome proliferator activated receptor gamma coactivator 1α (PGC1α; 2.61-fold), phospho-AMP-activated protein kinase (p-AMPK; 1.35-fold) and phospho-liver kinase B1 (p-LKB1; 1.41-fold), whereas it decreased the AMP/ATP ratio (from 4.25 to 1.82). CONCLUSION: The present study demonstrated the protective effects of berberine against insulin resistance induced by fructose. Our findings may provide an experimental basis for the application of berberine in the treatment of insulin resistance.